Inhibition of BACE2 counteracts hIAPP‐induced insulin secretory defects in pancreatic β‐cells. Issue 1 (23rd October 2014) - Alcarraz‐Vizán, Gema; Casini, Paola; Cadavez, Lisa; Visa, Montse; Montane, Joel; Servitja, Joan‐Marc; Novials, Anna
Abstract : BACE2 (β‐site APP‐cleaving enzyme 2) is a protease localized in the brain, where it appears to play a role in the development of Alzheimer disease (AD). It is also found in the pancreas, although its biologic function is not fully known. Amyloidogenic diseases, including AD and type 2 diabetes mellitus (T2D), share the accumulation of abnormally folded and insoluble proteins that interfere with cell function. Islet amyloid polypeptide (IAPP) deposits are a key pathogenic feature of T2D. Within this context, we found by global gene expression profiling that BACE2 was up‐regulated in the rat pancreatic β‐cell line INS1E stably transfected with human IAPP gene (hIAPP‐INS1E). Glucose‐stimulated insulin secretion (GSIS) in hIAPP‐INS1E cells was 30% lower than in INS1E cells. Additionally, INS1E cells transfected with a transient overexpression of BACE2 showed a 60% decrease in proliferation, a 3‐fold increase in reactive oxygen species production, and a 25% reduction in GSIS compared to control cells. Remarkably, silencing of endogenous BACE2 in hIAPP‐INS1E cells resulted in a significant improvement in GSIS (3‐fold increase vs. untransfected cells), revealing the significant role of BACE2 expression in β‐cell function. Thus, BACE2 inhibition may be useful to recover insulin secretion in hIAPP‐INS1E defective cells and may be proposed as a therapeutic target for T2D.‐ Montane, J., Servitja, J.‐M., Novials, A. Inhibition of BACE2 counteracts hIAPP‐induced insulin secretory defects in pancreatic β‐cells. FASEB J. 29, 95–104 (2015). www.fasebj.org